Seed germination of Carex lainzii Luceño, E. Rico & T. Romero: An endemic Spanish endangered species - KAROLINE APARECIDA FELIX RIBEIRO; CRISTIAN MADEIRA DE MEDEIROS; JOSÉ ÁNGEL SÁNCHEZ-AGUDO; JOSÉ SÁNCHEZ-SÁNCHEZ (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ribeiro KAF, Madeira de Medeiros C, Agudo JAS, Sánchez JS. 2019. Seed germination of Carex lainzii Luceño, E. Rico & T. Romero: An endemic Spanish endangered species. Biodiversitas 20: xxxx. Strategies to halt the decline of biodiversity include: in-situ and ex-situ conservation, the latter already considered at the global level essential in conservation programs. The results of the germinative responses of Carex lainzii Luceño, E. Rico & T. Romero (Cyperaceae), an endemic Spanish endangered species, are presented in this work, to different trials carried out in the laboratory with seeds harvested in the two known populations of that community. Treatments with and without 0.2% potassium nitrate (KNO3) were tested for four, six and eight months in cold stratification at 5 °C in two germination chambers at different temperatures (22/10 °C and 27/15 °C with a photoperiod of 12/12 hours). The results indicate that there is a large difference in germination rates between the two populations. The use of KNO3 did not increase germination rates in any case, but differences were found between periods of cold stratification, with six months being the most effective. On the other hand, the germination rates of both populations remain low (17.58% and 2%) compared to the obtained rate of seed viability. With this first approach to the understanding of the germination requirements of C. lainzii, it becomes clear that new essays are needed to obtain better results, in order to effectively implement the protection plans of C. lainzii populations.